Genetically programmed retinoic acid deficiency during gastrulation phenocopies most known developmental defects due to acute prenatal alcohol exposure in FASD - Petrelli, B.; Oztürk, A.; Pind, M.; Ayele, H.; Fainsod, A.; Hicks, G. G. (Frontiers in Cell and Developmental Biology, 2023)
Fetal Alcohol Spectrum Disorder (FASD) arises from maternal consumption of alcohol during pregnancy affecting 2-5% of the Western population. In Xenopus laevis studies, we showed that alcohol exposure during early gastrulation reduces retinoic acid (RA) levels at this critical embryonic stage inducing craniofacial malformations associated with Fetal Alcohol Syndrome. A genetic mouse model that induces a transient RA deficiency in the node during gastrulation is described. These mice recapitulate the phenotypes characteristic of prenatal alcohol exposure (PAE) suggesting a molecular etiology for the craniofacial malformations seen in children with FASD. Gsc+/Cyp26A1 mouse embryos have reduced RA activity and delayed HoxA1 and HoxB1 expression at E8.5. These embryos also show aberrant neurofilament expression during cranial nerve formation at E10.5 and have significant FASD sentinel-like craniofacial phenotypes at E18.5. Gsc+/Cyp26A1 mice develop severe maxillary malocclusions in adulthood. Phenocopying the PAE-induced developmental malformations with a genetic model inducing RA deficiency during early gastrulation strongly supports the alcohol/vitamin A competition model as a major molecular etiology for the neurodevelopmental defects and craniofacial malformations seen in children with FASD.